The study of evaluating the impact of service quality on customer loyalty in the hotel industry - Iyengar, Dr. M. Srividya (Revista Interdisciplinar de Ciência Aplicada, 2025)
Global tourism and economic development depend greatly on the hospitality sector, particularly the hotel industry. Service Quality plays a pivotal role in analyzing customer satisfaction, delight and eventually, the customer becomes loyal. This research seeks to explore the unique dynamics and challenges of the hospitality sector, specifically service marketing in the hotel industry of Southern India. This study, which is based on a mixed-methods methodology including qualitative interviews, quantitative data analysis and a literature review, offers insights into successful service marketing strategies. A sample size of 400 data across South India has been used to analyze the study. Therefore, the findings of this study can assist industry practitioners, hoteliers and policymakers in promoting customer satisfaction and optimizing business operations in the hospitality industry. The novelty is that the study was conducted in and around Southern part of India. Implications unfold the significance both in the realm of academia and in the practical domain of the service industry. Limitations are the sample size, which was taken as 400, could be more to verify the study more accurately & the study was conducted in the Southern part of India, could be done in other parts also to verify the study more accurately.